Kajian Literatur Sistematis: Alat Pengukuran Intensitas Getaran Akibat Aktivitas Transportasi: Systematic Literature Review: Measuring Tools for Vibration Intensity Due to Transportation Activities - Dewi; Mahmudah, Amirotul MH; Pangalapan Tua, Pasaribu Satria (Jurnal Teknik Sipil : Rancang Bangun, 2025)
Transport is a tool that plays an important role in society to help move people, goods and services. Improving the economic, tourism and social sectors is one of the positive impacts of transport. Behind the many positive impacts, transport activities have a negative impact in the form of vibrations that affect the surrounding environment. Vibration caused by transport activities can interfere with public comfort and health and cause damage to surrounding infrastructure. This proves that mitigation of vibration impacts is an important thing to do, especially vibration due to transportation activities. Vibration mitigation begins with obtaining measurable and reliable data. The data will be compared with the vibration quality standard regulations that apply in each region. Therefore, it is important to gain an understanding of the use of vibration intensity measuring devices, especially due to transportation activities that have been used by recent researchers. This article is a systematic literature review. The purpose of this article is to find out the application of various vibration measuring devices and analysis methods that can be used. From this goal, it is hoped that it can be a consideration for further research in choosing the vibration measuring device and measurement method to be used.